A study of the diimmonium dyes employing bis(fluorosulfonyl)imide anions for NIR absorbing film of CMOS image sensor. (June 2021) - Kim, Hong Mo; Lee, Hae Jung; Lee, Hyun Kyu; Hwang, Tae Gyu; Namgoong, Jin Woong; Lee, Jae Moon; Kim, Suhyeon; Kim, Jae Pil
Abstract: Near-infrared (NIR) absorbing film is one of the principal components of CMOS (complementary metal oxide semiconductor) image sensors to make the images photographed by a camera the same as the images perceived by the human eye. In this study, we have developed a series of diimmonium dyes that broadly and strongly absorb the near-infrared region. The diimmonium dyes were synthesized by introducing bis(fluorosulfonyl)imide counter anions. The synthesized diimmonium dyes showed solvatochromism depending on the polarity of solvents. The absorptivity and the maximum absorption wavelength of diimmonium dye were changed by the solvent polarity. The thermal stability of diimmonium dye was affected by the stability of the counter anion. Diimmonium dyes have been applied to the NIR absorbing films. The absorption spectra of NIR absorbing films made of different dyes showed similar positions of the absorption band. The absorbance of NIR absorbing films prepared with MC showed much higher absorbance than the films processed with MEK. Consequently, it is demonstrated that modification of counter anions of diimmonium dye affects the absorptivity and thermal stability of diimmonium dyes. Graphical abstract: Image 1 Highlights: A series of diimmonium dyes have been synthesized using bis(fluorosulfonyl)imide anions. The synthesized dyes showed high molar absorptivity except for in highly polar solvent and solvatochromism depending on solvent polarity. The synthesized dyes showed high thermal stability for the fabrication process of the NIR absorbing film of CMOS image sensor. The NIR absorbing film composed of diimmonium dyes and a transparent binder showed a great NIR blocking ability and visible light transmittance.